Association Between Breast Arterial Calcifications Found on Mammography and Increased Risk of Coronary Artery Calcifications in Asian Populations: A Literature Review - Aulia Wiratama Putra; Tasya Khalis Ilmiani; Dinda Ariesta; Evan Nugroho; Bagas Wahyu Utama; Ayers Gilberth Ivano Kalaij (Indonesian Journal of Global Health Research, 2026)
Mammography examination of the breast has been widely used throughout the world, but many findings found through this modality have been overlooked, one of which is breast arterial calcification (BAC). Breast cancer is often experienced by millions of women in the world, signs are usually screened for breast cancer using mammography. This literature review aims to assess the association between BAC found on mammography and increased risk of coronary artery calcifications in Asian populations. An initial search was carried out using reference sources from the electronic databases PubMed, Scopus, Cochrane, Wiley, ScienceDirect, EBSCOhost, and Google Scholar, using keywords "mammography", "breast arterial calcification", and "coronary artery disease" with their synonyms. Titles and abstracts were reviewed for relevance, followed by full-text screening, without any time limitation (until September 21th, 2023). The inclusion criteria was study published in English that assess BAC on mammography with the risk of coronary arterial calcifications in Asian. This review included a total of eight studies, which included a total of 2735 patients. Research was conducted in several countries in Asia, including Saudi Arabia, Nepal, Iran, China, South Korea, and Turkey, using cohort and cross-sectional research methods. BAC+ women were significantly older than BAC− women (P=0.001), and there was a strong association between BAC and CACS (P = 0.0001). The sign of BAC on mammography may contribute as a non-invasive marker of cardiovascular risk, especially in Asian populations. However, lack of a standardized BAC scoring system might limit its application. Breast artery calcification significantly increases the incidence of cardiac artery disease in Asian populations, which can be assessed by mammography and requires further attention from physicians.